Control of Neuronal Excitability by Calcium Binding Proteins: A New Mathematical Model for Striatal Fast-Spiking Interneurons - Bischop, Don Patrick; Orduz, David; Lambot, Laurie; Schiffmann, Serge N.; Gall, David (Frontiers in Molecular Neuroscience, 2012)
Calcium binding proteins, such as parvalbumin (PV), are abundantly expressed in distinctive patterns in the central nervous system but their physiological function remains poorly understood. Notably, at the level of the striatum, where PV is only expressed in the fast-spiking (FS) interneurons. FS interneurons form an inhibitory network modulating the output of the striatum by synchronizing medium-sized spiny neurons (MSN). So far the existing conductance-based computational models for FS neurons did not allow the study of the coupling between PV concentration and electrical activity. In the present paper, we propose a new mathematical model for the striatal FS interneurons that includes apamin-sensitive small conductance Ca2+-dependent K+ channels (SK) and the presence of a calcium buffer. Our results show that a variation in the concentration of PV can modulate substantially the intrinsic excitability of the FS interneurons and therefore may be involved in the information processing at the striatal level.